Pengaruh Digital Games Learn Math and Math Problems Terhadap Motivasi Belajar Matematika Dipandang dari Neuroscience - W.S., Fransiska Duitasari; Safitri, Putri (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Neuroscience is the study of how the nerves of the brain work. The brain's nervous system can influence a person's positive emotions that become the impetus to do something. In Mathematics, a person's willingness to learn is influenced by the brain's response based on the stimulus received in learning. Fun Mathematics learning can have a big impact on students. To make learning Mathematics fun, teachers can use an interesting learning media such as digital-based games. This article examines the use of digital games “Learn Math and Math Problems” (LMaMP) in learning Mathematics in Grade X students at a private school in Yogyakarta and Grade X and XI students at a private school in Surakarta. This research is qualitative. The method used is observation, documentation, interviews and literature study. The purpose of the study was to find out how one of the digital games LMaMP works in terms of neuroscience and its effect on students' learning motivation. The results showed that the use of LMaMP digital games could make students more motivated in learning Mathematics because the activity in the games gives the positive stimulus for the brain and activates the limbic cortex system.